Trim14 promotes autophagy and chemotherapy resistance of gastric cancer cells by regulating AMPK/mTOR pathway. Issue 5 (25th February 2020) - Xiao, Feng; Ouyang, Binshen; Zou, Jue; Yang, Yelin; Yi, Lina; Yan, Hongzhu
Abstract: Objective: To study the relationship between TRIM14 expression and chemotherapy resistance of gastric cancer (GC) cells. Methods: The expression of TRIM14 in 5‐fluorouracil (5‐FU)‐ and oxaliplation (L‐OHP)‐resistant GC tissues and cells were determined by qRT‐PCR and western blotting. PcDNA3.1‐TRIM14 and shRNA‐TRIM14 vector were transfected to 5‐FU‐resistant GC cells (SGC7901/5‐FU), and the proliferation and apoptosis of cells were measured. Animal experiments on 5‐FU‐resistant GC mice were performed to study the effect of TRIM14 expression on tumor size and weight, GC cell migration, and proliferation. pcDNA3.1‐MK‐3903 plasmid was transfected to SGC7901/5‐FU cells with TRIM14 silence. The cell proliferation and apoptosis were determined. The protein expressions of Trim14, LC3, and BECLIN1 were measured by western blotting. Results: TRIM14 was significantly upregulated in 5‐FU‐ and L‐OHP‐resistant GC tissues and cells. The overexpression of TRIM14 promoted the proliferation and autophagy of SGC7901/5‐FU cells, and inhibited the apoptosis. Moreover, in vivo experiment verified that the silence of TRIM14 reduced the tumor size and weight, and inhibited the migration and proliferation of GC cells in 5‐FU‐resistant GC mice. The overexpression of MK‐3903 reversed the inhibiting role of TRIM14 knockout on the proliferation and autophagy of SGC7901/5‐FU cells. Conclusion: TRIM14 promoted chemotherapy resistance of GC cells by regulating AMPK/mTOR pathway, and may be a new biomarker for treating GC.